PENDEKATAN AURAL ORAL DALAM KETERAMPILAN BERBICARA - Fajriah (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2022)
One of the Arabic language skills that must be mastered by students is speaking skiil (maharah al-kalam), namely the ability of students to use Arabic sounds (ashwath ‘arabiyyah) appropriately by using grammar (qawa’id nahwiyyah wa sharfiyyah), and arranging word –by- word. So that, it can be used to express what they want. One of the approaches that can be used in learning speaking skiils is the Aural Oral Approach. In Arabic it is called al-madkhal al-sam’i al-syafahi,which is an approach that has the assumption that language is what both heard and spoken. While writing is only representation of speech. In this approach, the learning process is more focused on listening (hearing) and imitating (pronouncing) activities according to what the teacher (native speaker) says. The results that wiil be achieved through this approach are not only mastering spoken language and listening spontaneously, but also being able to master reading and writing skills. Among the advantages of this approach are that students have good pronunciation. They are able to make standard sentence patterns that have been trained. They can carry out oral communication well. On the contrary, there are some weaknesses toward the Aural Oral Approach. The student’s responses are mecanistc. The do not realize, understand or think the real meaning of the spoken statement.